EVALUASI PELAKSANAAN PERATURAN DAERAH NOMOR 08 TAHUN 2008 TENTANG ORGANISASI DAN TATA KERJA KECAMATAN DI KABUPATEN KUTAI BARAT - Tony Anggara (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
This article describe and analyze the evaluation of West Kutai District Regulation No. 08 Year 2008 on Organization and Work Procedure In the District of Kutai Barat and explain the factors supporting and inhibiting. This study focused on the effectiveness organiasasi, organizational efficiency, organizational performance, and justice organizations. This study is qualitative descriptive. Data was obtained through interviews, observation and document, and then analyzed using an interactive model. The results of the study explained that the effectiveness of the organizational structure, less equally effective in the tasks and functions of planning. Organizational Structure Efficiency, inefficient execution of tasks because of time and energy is used only for financial affairs.Keyword : Evaluation, Organization and Working Procedure, West Kutai.